HUBUNGAN SELF DIRECTED LEARNING READINESS (SDLR) DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA ANGKATAN 2015 FAKULTAS KEDOKTERAN UNIVERSITAS MALAHAYATI BANDAR LAMPUNG - Anggunan Anggunan; Sri Maria Puji Lestari; Bagas Aryo Pangestu (Program Studi Psikologi Universitas Malahayati, 2020)
THE RELATIONSHIP BETWEEN SELF DIRECTED LEARNING READINESS (SDLR) AND ACADEMIC PROCRASTINATION AMONG COLLEGE STUDENTSThis study aims to determine the relationship between Self-Direct Learning Readiness (SDLR) with academic procrastination in college students. This research is a quantitative study with analytic survey design and cross sectional approach. The sample of this study was 174 students of the Faculty of Medicine, University of Malahayati, class of 2015. The research data were obtained with the SDLR scale and academic procrastination scale. The data obtained were processed using Pearson Product Moment correlation test. The results showed a significant negative correlation between Self-Direct Learning Readiness and academic procrastination, which means the greater the score of Self-Direct Learning Readiness, the lower the Academic Procrastination. The results of this study have implications for educational institutions to develop Self Directed Learning Readiness (SDLR) in students in order to prevent the emergence of academic procrastination.Penelitian ini bertujuan untuk mengetahui hubungan antara Self-Direct Learning Readness (SDLR) dengan prokrastinasi akademik pada mahasiswa. Penelitian ini merupakan penelitian kuantitatif dengan rancangan survei analitik dan pendekatan cross sectional. Sampel penelitian ini adalah 174 mahasiswa Fakultas Kedokteran Universitas Malahayati angkatan 2015. Data penelitian diperoleh dengan skala SDLR dan skala prokrastinasi akademik. Data yang diperoleh diolah menggunakan uji korelasi Pearson Product Moment. Hasil penelitian menunjukkan adanya korelasi negatif yang signifikan antara Self-Direct Learning Readness dengan prokrastinasi akademik yang artinya semakin besar skor Self-Direct Learning Readness akan semakin rendah Prokrastinasi Akademik. Hasil penelitian ini memberi implikasi bagi institusi pendidikan untuk mengembangkan Self Directed Learning Readiness (SDLR) pada mahasiswa agar dapat mencegah munculnya prokrastinasi akademik.